(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Training with rubber ropes is one of the modern training methods that help to develop the absolute strengthof specific parts of the body and according to the skill performance, especially when training with differentmuscle moments that cause the movement of those limbs according to variable resistances, especially forwheelchair tennis players, so the research was applied to a sample of tennis players with chairs Using theseexercises to find out their effect on the serve skill mechanism, this exercises were applied for a period of (10)weeks, on (6) players who are the best players in this competition, and the researcher used foreign and Arabsources and the international information network, observation, experimentation, tests and measurements asmeans of collecting information.A video camera for filming and using kinematic analysis to extract the mechanical variables, and theresearcher came up with several conclusions, including that training according to the results of the analysisand using the change of resistance arms when training with rubber ropes was effective in developing thespeed of the centers of the striking arm parts of the research sample. The exercises led to an improvement inthe technical performance interdependence (the research sample), which inevitably affected the achievementof good achievement, as well as in improving the response time of the research sample